From royal family-based ownership to state business management: Mangkunegara's sugar industry in Java from the middle of the 19th to early 20th century. Issue 2 (3rd April 2019) - Wasino,; Hartatik, Endah Sri; Nawiyanto,
ABSTRACT: This article discusses the dynamics of the sugar industry owned by an indigenous ruler of the Mangkunegaran principality of Surakarta from the mid-19 th to early 20 th century in Java, Indonesia. It draws mainly upon source materials from the Mangkunegara`s collection in Indonesia and colonial archives in the Hague, Netherlands. The purposes of the article are to elaborate the development of the Mangkunegaran sugar industry, to look at how the business operated, and the strategies to run the business profitably and to deal with market fluctuations. It is argued that starting as a Javanese royal family plantation venture, the top management was on the hand of royal family aided by European managers. After the death of Mangkunegara IV, the efforts to build the economic foundations of the Mangkunegaran principality experienced a great shock. To get out safely from the crisis, a reorganization of the management of Mangkunegaran sugar industry was underway. The management was entrusted to the European superintendent at the top-level and European managers at the factory level. There was also clear financial separation between the sugar industry and the Mangkunegaran government ( Praja ). Interestingly, the process also involved the resident of Surakarta as representative of the Dutch colonial government.